1999
DOI: 10.1002/(sici)1097-4660(199906)74:6<527::aid-jctb77>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

The effect ofD-glucose on milk clotting activity ofMucor miehei in a chemostat with biomass retention

Abstract: In this study microbial production of rennin from a commercial strain of Mucor miehei (NRRL 3420) has been accomplished in a continuously fed fermenter. The effects of feed D-glucose concentration (2.5±30 g dm À3) on milk clotting activity and on other system variables were investigated at optimum mixing and dilution rates of 400 rpm and 0.0052 h À1 , respectively, without pH control. Maximum milk clotting activity (1.24 IU cm À3) occurred when the feed D-glucose concentration was 7.5 g dm À3. Enzyme productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Beyenal et al (1999);Seker et al(1999), Silveira and Contiero (2001) also observed this fact. The use of baffled flasks permited more aeration with an increased in the growth and a decrease in the enzyme production.…”
Section: Sugar Determinationmentioning
confidence: 68%
“…Beyenal et al (1999);Seker et al(1999), Silveira and Contiero (2001) also observed this fact. The use of baffled flasks permited more aeration with an increased in the growth and a decrease in the enzyme production.…”
Section: Sugar Determinationmentioning
confidence: 68%
“…behavior. Seker et al (1998) and Beyenal et al (1999), who worked on the production of the aspartic proteinase from R. miehei, pointed out that a high glucose concentration in the fermentation media inhibited enzyme activity, as it stimulated biomass rather than rennin production. Silveira et al (2005) also investigated the effect of carbon and nitrogen sources on rennin production by R. miehei in submerged fermentation.…”
mentioning
confidence: 99%